Annual Report on Exchange Arrangements and Exchange Restrictions 1966. (Annual Report on Exchange Arrangements and Exchange Restrictions, 1966)
This paper discusses developments in individual countries reflected domestic policies, but also the way in which their economies were affected by international economic developments. Generally, countries that have assumed the obligations of Article VIII of the IMF Agreement-and which as noted in the last Report account for some 70 per cent of world trade-were making less use of restrictions, and some were able further to reduce that use in 1965-1966. At the outset of 1965 there were a number of disturbing tendencies in the international payments situation. The growth of international trade was noticeably slackening, and the prices of primary products were declining. Among the industrial countries export increases in 1965 were generally largest for those whose payments positions were already strong and whose restrictions on payments had been largely eliminated. Thus, the member countries of the European Economic Community (EEC) had a very satisfactory expansion of exports; this was partly associated with economic developments in France and Italy, where some easing of domestic demand released resources for export.